Awareness is in the eye of the observer: Preserved third-person awareness of deficit in anosognosia for hemiplegia. (6th June 2022) - Besharati, Sahba; Jenkinson, Paul M.; Kopelman, Michael; Solms, Mark; Moro, Valentina; Fotopoulou, Aikaterini
Abstract: In recent decades, the research traditions of (first-person) embodied cognition and of (third-person) social cognition have approached the study of self-awareness with relative independence. However, neurological disorders of self-awareness offer a unifying perspective to empirically investigate the contribution of embodiment and social cognition to self-awareness. This study focused on a neuropsychological disorder of bodily self-awareness following right-hemisphere damage, namely anosognosia for hemiplegia (AHP). A previous neuropsychological study has shown AHP patients, relative to neurological controls, to have a specific deficit in third-person perspective taking and allocentric stance (the other unrelated to the self) in higher order mentalizing tasks. However, no study has tested if verbal awareness of motor deficits is influenced by perspective-taking and centrism and identified the related anatomical correlates. Accordingly, two novel experiments were conducted with right-hemisphere stroke patients with (n = 17) and without AHP (n = 17) that targeted either their own (egocentric, experiment 1) or another stooge patients (allocentric, experiment 2) motor abilities from a first-or-third person perspective. In both experiments, neurological controls showed no significant difference in perspective-taking, suggesting that social cognition is not a necessary consequence of right-hemisphere damage. More specifically, experiment 1 found AHP patients more aware of their own motor paralysis (egocentric stance) when asked from a third compared to a first-person perspective, using both group level and individual level analysis. In experiment 2, AHP patients were less accurate than controls in making allocentric judgements about the stooge patient, but with only a trend towards significance and with no difference between perspectives. As predicted, deficits in egocentric and allocentric third-person perspective taking were associated with lesions in the middle frontal gyrus, superior temporal and supramarginal gyri, and white matter disconnections were more prominent with deficits in allocentricity. Behavioural and neuroimaging results demonstrate the intersecting relationship between bodily self-awareness and self-and-other-directed metacognition or mentalisation. Highlights: This study focused on a disorder of bodily self-awareness following right-hemisphere damage- anosognosia for hemiplegia (AHP). Two novel experiments were conducted to test the potentially distinct role of perspective taking and allocentricity in self-awareness. AHP patients were more aware of their own paralysis (egocentric stance) when asked from a verbal third-person perspective. Deficits in egocentric and allocentric third-person perspective taking were associated with lesions in the middle frontal gyrus, superior temporal and supramarginal gyri. Findings suggest that self-awareness in AHP involves a dissociation between the first-person, egocentric perspective and third-person, allocentric metacognitive beliefs.